(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
In the present era, people does not purchase mobile phones just to remain in touch rather youth today use it to express their thoughts via social networking, play games, read news, surf on the internet, listen to music, chat instantly with friends & families and even use it for e-commerce activities. Competition among the cell phone companies becomes fierce today rapid transformation in the technology. All companies used to launch their upgraded model within a very short period of time to remain ahead in the competition. This has decreases the life cycle of the model and on the other hand gives a wide variety to the consumers for purchasing. Increasing variety and competition leads to put pressure on price and results in decrease in the profit margin of the companies. To decrease the overall cost, companies started shrinking their distribution channels and make presence over internet either through their own web sites (Xiaomi) or through online retailers (egFlipkart, Amazon). Thus, studying online buying behavior of the consumers becomes vital for the marketers so as to attract more pool of customers. This paper is useful in understanding the online buying behavior of students when they undergone process of cell phone purchasing.